2014
DOI: 10.15680/ijirset.2014.0311007
|View full text |Cite
|
Sign up to set email alerts
|

Regression Correlation Analysis between GBH and Carbon Stock of Major Tree Species in Dharoi Range, Gandhinagar Forest Division, India

Abstract: Aim of this study is to analyse the regression correlation between GBH and Carbon stock in the major tree species of Dharoi Range, Gandhinagar Forest Division. Major ten dominant tree species in Dharoi range were selected for study. Total biomass and carbon sequestered in the major tree species have been estimated using nondestructive method. Based on this analysis and interpretation the allometric model is prepared which will be helpful to estimate carbon stock of major tree species by Girth at Breast Height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The study on the regression correlation analysis between GBH and Carbon stock was carried out in the major tree species of Dharoi Range, Gandhinagar Forest Division. The results indicated that GBH-Carbon Stock relationship showed relatively higher R2 values; and based on this a allometric model was developed which showed that GBH alone can safely be used to estimate carbon stock of major tree species in Dharoi Range (Jaiswal, et al, 2014 (Tripathi et al, 2010).…”
Section: Integrated Application Of Remote Sensing and Gis For Carbon Sequestrationmentioning
confidence: 99%
“…The study on the regression correlation analysis between GBH and Carbon stock was carried out in the major tree species of Dharoi Range, Gandhinagar Forest Division. The results indicated that GBH-Carbon Stock relationship showed relatively higher R2 values; and based on this a allometric model was developed which showed that GBH alone can safely be used to estimate carbon stock of major tree species in Dharoi Range (Jaiswal, et al, 2014 (Tripathi et al, 2010).…”
Section: Integrated Application Of Remote Sensing and Gis For Carbon Sequestrationmentioning
confidence: 99%